2009
DOI: 10.1096/fj.09-145508
|View full text |Cite
|
Sign up to set email alerts
|

Acid ceramidase improves the quality of oocytes and embryos and the outcome of in vitro fertilization

Abstract: A major challenge of assisted reproduction technologies (ARTs) is to mimic the natural environment required to sustain oocyte and embryo survival. Herein, we show that the ceramide-metabolizing enzyme, acid ceramidase (AC), is expressed in human cumulus cells and follicular fluid, essential components of this environment, and that the levels of this enzyme are positively correlated with the quality of human embryos formed in vitro. These observations led us to develop a new approach for oocyte and embryo cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Ceramide also has been shown to play a central role in the age-related acceleration of apoptosis in the female germline [10, 11]. In our previous publication [5], we showed that in human oocytes AC co-localizes with membranes, the meiotic spindle, and DNA, thus supporting its potential role in preventing cell cycle arrest. Recent reports also have shown that apoptosis in the ovaries of several species can be prevented by S1P, a downstream product of AC activity [11, 12, 29].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Ceramide also has been shown to play a central role in the age-related acceleration of apoptosis in the female germline [10, 11]. In our previous publication [5], we showed that in human oocytes AC co-localizes with membranes, the meiotic spindle, and DNA, thus supporting its potential role in preventing cell cycle arrest. Recent reports also have shown that apoptosis in the ovaries of several species can be prevented by S1P, a downstream product of AC activity [11, 12, 29].…”
Section: Discussionsupporting
confidence: 62%
“…We have further shown by immunohistochemical, western blotting and enzymatic activity assays that AC is expressed in human and murine oocytes and/or follicular fluid, and that its expression levels decline during oocyte culture. In addition, supplementation of AC into media improved the survival rates and quality of oocytes and embryos grown in vitro , as well as embryo development in vivo after implantation [5]. …”
Section: Introductionmentioning
confidence: 99%
“…As noted above, observations on the early embryonic lethality of the complete AC knockout mouse led to the use of rhAC to enhance the outcome of in vitro fertilization (IVF) (Eliyahu et al, 2010). Supplementation of mouse IVF culture media with rhAC resulted in approximately twofold more embryos than obtained using standard culture conditions.…”
Section: In Vitro Uses Of Recombinant Acid Ceramidasementioning
confidence: 99%
“…AC knockout mice do not survive beyond the 2-cell stage and undergo apoptotic death (Eliyahu et al 2007). Recent findings show that AC improves the quality of oocytes and embryos and the outcome of in vitro fertilization (Eliyahu et al 2010).…”
Section: Farber Diseasementioning
confidence: 99%